Strategi Promosi Aplikasi Motorku Express Berdasarkan Analisis SWOT - Lusiana, Indah; Novitaningtyas, Ivo (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
Nowadays digital technology provides benefits for the business development process in a company. Astra Motor Kedungsari Magelang also utilizes digital technology through the Motorku Express application service. This service is a form of appreciation for all Astra Motor Kedungsari Magelang customers. However, not all customers know the usefulness of the Motorku Express application. Therefore Astra Motor Kedungsari Magelang requires a strategy to promote the Motorku Express application to customers in order to increase the effectiveness of the application utilization. This study aims to analyze the strengths, weaknesses, opportunities, and threats of the Motorku Express application based on SWOT analysis to formulate a promotion strategy. This research is a qualitative descriptive study that uses interviews, observation, and literature review as a method of data collection. The results of the SWOT analysis show that the formulation of strategies that can be applied is the WO strategy by increasing promotion strategies using mass selling by utilizing social media such as WhatsApp, Instagram, Twitter, Facebook, Line, E-mail, radio, television, and Youtube as promotional tools, conducting sales promotion strategies by giving discounts or even free service discounts by using the Motorku Express application for one year specifically to purchase a motorbike at Astra Motor, attend events for promotion, free shipping costs to attract consumers and offers purchasing programs every month.